2020
DOI: 10.1136/bmj.m4381
|View full text |Cite
|
Sign up to set email alerts
|

Patient mortality after surgery on the surgeon’s birthday: observational study

Abstract: Objective To determine whether patient mortality after surgery differs between surgeries performed on surgeons’ birthdays compared with other days of the year. Design Retrospective observational study. Setting US acute care and critical access hospitals. Participants 100% fee-for-service Medicare beneficiaries aged 65 to 99 years who underwent one of 17 common em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
0
19
1
Order By: Relevance
“…However, it was significantly lower than the rate shown by studies conducted in Nigeria (8.3%) and United states (7.0%), 17 , 18 . This might be due to variations in study duration, socio-demographic characteristics of participants and urbanisation levels of the study area.…”
Section: Discussioncontrasting
confidence: 65%
“…However, it was significantly lower than the rate shown by studies conducted in Nigeria (8.3%) and United states (7.0%), 17 , 18 . This might be due to variations in study duration, socio-demographic characteristics of participants and urbanisation levels of the study area.…”
Section: Discussioncontrasting
confidence: 65%
“…Patient postoperative 30-day mortality (also called 30-day postoperative mortality), a meaningful indicator of perioperative outcome, is defined as death within 30 days after surgery. It is not only the adjustment for patient characteristics and surgeon fixed effects, but also an effective evaluation of access to safety of the anesthesia and operation [1,2]. Previous studies reported that 30-day postoperative mortality varied from 0.95 to 8.62% [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The Super Bowl stock market predictor is nonsensical and has not worked since it was first reported, but worked initially P rovocative research findings are often widely publicised. It has been reported, for example, that the stock market usually goes up if certain teams win the Super Bowl; 1 femalenamed hurricanes are deadlier than those with male names; 2,3 Asian-Americans are prone to heart attacks on the fourth day of the month; 4,5 surgeries are more likely to be fatal if they are done on the surgeon's birthday; 6,7 and traffic accidents surge on Friday the 13th. 8 The claim that fatal motorcycle accidents are more likely when there is a full moon is a compelling example of what Gelman and Loken call a "garden of forking paths".…”
mentioning
confidence: 99%
“…Provocative research findings are often widely publicised. It has been reported, for example, that the stock market usually goes up if certain teams win the Super Bowl; 1 female‐named hurricanes are deadlier than those with male names; 2,3 Asian‐Americans are prone to heart attacks on the fourth day of the month; 4,5 surgeries are more likely to be fatal if they are done on the surgeon's birthday; 6,7 and traffic accidents surge on Friday the 13th 8 …”
mentioning
confidence: 99%